THE IMPACT OF DIGITAL HUMAN RESOURCE MANAGEMENT STRATEGIES ON ENHANCING ORGANIZATIONAL AGILITY: AN ANALYTICAL STUDY AT THE UNIVERSITY OF SUMER / COLLEGE OF ADMINISTRATION AND ECONOMICS - Amal Jaber Fzaea (PT. Antis International Publisher, 2026)
Objective: This study aimed to examine the impact of Digital Human Resource Management (DHRM) strategies on organizational agility at the College of Administration and Economics, University of Sumer, in light of the growing trends of digital transformation in higher education institutions and the increasing need for universities to respond rapidly to environmental changes. Method: The study adopted a descriptive-analytical approach and employed a structured questionnaire based on validated measures from previous studies. Data were collected from a random sample of 80 academic and administrative staff members. Data analysis was conducted using the Statistical Package for Social Sciences (SPSS V.26) through descriptive statistics, normality testing, and simple and multiple linear regression analyses. Results: The findings revealed a high level of adoption of digital human resource management strategies, as well as a high level of organizational agility. The results also confirmed a statistically significant positive impact of DHRM strategies, including digital recruitment, digital training and development, digital performance management, HR analytics, and employee self-service systems, on organizational agility dimensions represented by sensing agility, decision-making agility, and implementation agility. Novelty: The study concluded that DHRM strategies represent an effective strategic mechanism for enhancing institutional flexibility and adaptability in higher education institutions. The study recommends strengthening digital infrastructure, expanding data-driven HR practices, and investing in continuous digital training programs to enhance organizational agility.